1993
DOI: 10.1109/77.233907
|View full text |Cite
|
Sign up to set email alerts
|

Persistent magnetic flux and mapping of intergranular junctions in melt textured YBa/sub 2/Cu/sub 3/O/sub 7/

Abstract: Abstnct--Melt textured superconductors have been prepared with a microstructure characterized by large domains having misaligned growth fronts. An rf mutual inductance miaoprobe has been developed which allows to identify and characterise the weak link behaviour of the high angle grain boundaries separating the domains. The mechanisms of flux penetration and trapping i n a single domain sample has been analysed in the H//c configuration at low temperature ( 25 K) where Jc is essentially field independent. A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…To our knowledge, but for a few reports [8]- [11], no detailed work has been reported at radio frequencies. An rf mutual inductance probe was used by Gomis et al [10] to characterize the weak link behavior of melt-textured HTS. From the analysis of the data the authors found that surface barrier effects are reduced in MT samples.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, but for a few reports [8]- [11], no detailed work has been reported at radio frequencies. An rf mutual inductance probe was used by Gomis et al [10] to characterize the weak link behavior of melt-textured HTS. From the analysis of the data the authors found that surface barrier effects are reduced in MT samples.…”
Section: Introductionmentioning
confidence: 99%